Present-day Spanish fashion lexicon dresses up in English - Rodríguez Arrizabalaga, Beatriz (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2017)
Lexical borrowings can be regarded as one of the clearest and most direct consequences of any language contact situation. However, not all the borrowings that enter a language are alike. Since their entrance in a given language is motivated by different reasons, two general kinds of borrowings must be distinguished: necessary borrowings which name ideas and concepts for which the recipient language does not have any equivalent term; and superfluous borrowings which, on the contrary, refer to realities for which the recipient language already has equivalent terms. This paper focuses on the latter type. Specifically, it presents a diachronic corpus-based analysis of 14 English fashion terms with a clear Spanish lexical counterpart —blazer/‘chaqueta’, celebrity/‘famoso’, clutch/‘bolso de mano’, cool/‘de moda’, fashion/‘moda’, fashionable/‘de moda’, fashionista/ ‘adicto a la moda’, jeans/‘vaqueros’, nude/‘color carne’, photocall/‘sesión de fotos’, shorts/‘pantalones cortos’, sporty/‘deportivo’, trench/‘trinchera, gabardina’, and trendy/‘moderno’— in four Spanish corpora: the Corpus del Español, and the CORDE, CREA and CORPES XXI corpora. My objectives are twofold: firstly, to demonstrate to what extent these unnecessary Anglicisms are increasingly becoming part of the everyday contemporary Peninsular Spanish fashion lexicon; and secondly, to account for the three reasons that underlie their alleged constant entrance in twenty-first century Peninsular Spanish: (i) globalization and the impact of English on Spanish; (ii) the highly visible presence of English in the field of advertising; (iii) and the selling power of English.